Temperature-dependent stress in diamond-coated AlGaN/GaN heterostructures. (15th September 2016) - Ižák, Tibor; Jirásek, Vít; Vanko, Gabriel; Dzuba, Jaroslav; Kromka, Alexander
Abstract: In this study, we present a complex methodology for evaluation of the thermally induced stress in patterned diamond microstructures. The diamond strips (2 mm in width and 0.78 or 2.8 μm in thickness) were selectively grown on AlGaN/GaN heterostructures. The stress was evaluated from the Raman shift of the diamond peak position within the temperature range from 50 to 400 °C. The shift was measured at two positions, i.e. at center and edge of the strip. The methodology for stress evaluation is based on the appropriate temperature correction of measured Raman spectra. We observed that for temperature increase from 50 to 400 °C the difference between stresses evaluated at the center and edge of diamond strip (Δstress) decreases from 0.27 to 0.18 GPa and from 0.32 to 0.1 GPa for the thinner and thicker diamond films, respectively. Experimental data were compared with FEM simulations. The simulations fitted well to experimental data and confirmed that the stress difference between the center and edge of diamond strip was caused by thermal stress component. As the temperature approaches the value close to the diamond deposition condition ( 700 °C), the stress becomes homogeneous and equal to the intrinsic stress induced after the diamond growth. Graphical abstract: Highlights: The thermally induced stress in diamond microstructures on AlGaN/GaN heterostructures were studied by Raman spectroscopy. Temperature correction was applied to exclude additional influences of temperature on Raman frequency modes. ΔStress across the diamond strip decreased with increasing temperature and revealed its homogeneous distribution. FEM simulations correlated with experimental data and developed methodology is more accurate for stress evaluation.